What do we know about corporate-startup engagement? A systematic review of the main modes of collaboration between corporations and startups - Kaique Sbampato; Adriano Proença; Edison Renato Silva (Innovation & Management Review, 2025)
Purpose The purpose of this article is to identify the predominant modes to realize corporate-startup engagement (CSE). Design/methodology/approach We carried out a systematic literature review to synthesize how startups and corporations collaborate in this form of innovation. Findings The authors found 19 CSE modes, which range from modes that involve less risk and are simpler to those that involve more risk and are more complex. Originality/value The findings consolidate the state of the art on the modes of CSE. It can help scholars drive novel research departing from consolidated findings, and practitioners can understand how collaboration between corporations and startups takes place and anticipate future challenges.
Keywords: 650; Corporate entrepreneurship; Corporate venturing; Innovation; Intrapreneurship; Startups